Partisipasi Masyarakat Dalam Rehabilitasi Lahan Pada Program Kebun Bibit Rakyat (KBR) di Desa Plukaran Kecamatan Gembong Kabupaten Pati - Dewi, Adinda Kusuma (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
In 2010 the Indonesian government established the KBR program (Kebun Bibit Rakyat – Community Nursery) through participatory rehabilitation and cultivation of critical, barren or unproductive lands. The program aimed to maintain the environmental carrying capacity, thus reducing forest and farmland degradation. The study examines community participation in the KBR program and its potential for sustainability in Plukaran Village, Gembong district, Pati Regency. The study combined quantitative and qualitative approach; sampling was conducted randomly and supported by interviews with selected informan. The study applies descriptive analysis using theories of participatory by Pomeroy and Williams (1994). The study has identified the level of community participation in the planning, commencement and evaluation of the program. At the planning stage, community participation varies from informing to consultation. At the commencement stage, community participation varies from informing, cooperation to community control. At the evaluation stage, it was found to be at the informing level. The study also found that the program has been commenced effectively, however, equity still needs to be attained in order to ensure the program’s sustainability.